Pendekatan penilaian untuk analisa cerun tanah - Zainal Abidin, Mohd. Hazreek (2006)
Soil Mechanics Theory establishes the current practice of designing a slope by founding the analysis on the ‘c’ and ‘Ø’ values. However, the theory still yields an anomalous result. Although in many real cases the engineer has designed slopes by using factor of safety greater than 1.5, but the slope failed. These facts prove the designed parameters are still inadequate to prevent slope failure. In this study, The Soil Mechanics Approach (e.g. Conventional Approach) will be compared to The Engineering Geology Approach for analyzing slope stability. The study is carried out for investigating other relevant parameters should be considered in designing a slope. All the required data that was used in both analyses was obtain from site (Gunung Pulai) and laboratory works. The results from both analyses shown that there was a difference in term of stability. The influence of relict joint that has been excluded in Soil Mechanics Approach has been detected as the main factor that cause the result that has been obtain inaccurate. The influence of relict joint is one of the main factors in the analysis of Engineering Geology Approach which gain a better result compared to the Soil Mechanics Approach. Each approaches takes into account different parameters in the analysis that suggest different influence factors affecting slope stability. For this reason, it is better to use both approaches (Soil Mechanics and Engineering Geology) in slope analysis containing relict joint.